Masculinity, Testosterone, and Financial Misreporting - JIA, YUPING; LENT, LAURENCE VAN; ZENG, YACHANG (Journal of accounting research, 2014)
We examine the relation between a measure of male CEOs' facial masculinity and financial misreporting. Facial masculinity is associated with a complex of masculine behaviors (including aggression, egocentrism, riskseeking, and maintenance of social status) in males. One possible mechanism for this relation is that the hormone testosterone influences both behavior and the development of the face shape. We document a positive association between CEO facial masculinity and various misreporting proxies in a broad sample of S&P1500 firms during 1996–2010. We complement this evidence by documenting that a CEO's facial masculinity predicts his firm's likelihood of being subject to an SEC enforcement action. We also show that an executive's facial masculinity is associated with the likelihood of the SEC naming him as a perpetrator. We find that facial masculinity is not a measure of overconfidence. Finally, we demonstrate that facial masculinity also predicts the incidence of insider trading and option backdating.